One-pot hydrothermal oxidation enables in situ construction of CDs/Ni(OH)2 composite for electrocatalytic oxygen evolution - Wang, Hui; Xu, Weijuan; Han, Xuan; Yan, Yue; Zhu, Bingxian; Wang, Zhiyuan; Wang, Libo; Zhao, Qingshan; Wu, Mingbo (Frontiers in Chemistry, 2025)
Electrochemical water splitting is a promising solution to energy challenges, yet the kinetically sluggish oxygen evolution reaction (OER) at the anode demands highly active and cost-effective catalysts. Herein, we develop a facile one-pot hydrothermal oxidation strategy to simultaneously achieve the oxidative cleavage of petroleum coke into nanoscale carbon dots (HO-CDs) and the in situ growth of nickel hydroxide (Ni(OH)2) on nickel foam (NF), yielding an HO-CDs-Ni(OH)2/NF composite catalyst. The in situ-formed HO-CDs efficiently modulate Ni(OH)2 crystallization by suppressing oriented growth to create a nanostructure with abundant active sites. This synergistic interplay significantly enhances both active site accessibility and charge transfer efficiency, leading to exceptional OER performance. The optimized HO-CDs-Ni(OH)2/NF catalyst delivers an overpotential of 353 mV at a current density of 50 mA cm-2 with a small Tafel slope of 81.2 mV dec−1. Furthermore, it demonstrates excellent stability, retaining 92% of its initial current density after a 24-h chronoamperometric test. This work presents a straightforward approach for designing high-performance transition metal-based electrocatalysts through carbon dot-mediated crystal engineering via in situ incorporation.